Images of Figure and Anagram Media Development In Optimization of Vocabulary Master - Agus Zainudin; Prima Cristi Crismono; Maryati Nutafia (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
Media Image and Anagram is an effort to optimize the mastery of Indonesian vocabulary for class I students of Madrasah Ibtidaiyah. This study uses Research and Development (R&D) research methods adapted into 7 Borg And Gall development models: (Potentials and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, and Product Revision). The population of this study was 26 students of class I MI Islamiyah Tempursari-Lumajang, who were divided into experimental and control groups. Data collection in this study used interviews, observations, questionnaires, and tests. The development of Pictures and Anagrams media resulted in Visual media products in the form of Stand Boards. Media product validation is carried out to determine the product's feasibility, the material validator's results get a score of 94, and the media design validator is 97. The Images of Figure and Anagram media are designed attractively to get a score of 95.3 in response to media attractiveness. In the t-test with a significance level, the results obtained 5% (2-tailed) 0.0001 < 0.05, meaning Ho is rejected and Ha is accepted, so there is a significant difference in increasing Indonesian vocabulary mastery between the experimental group using Pictures and Anagrams media with an impact group that did not use Pictures and Anagrams media.